1995
DOI: 10.1095/biolreprod52.4.759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Matrix Proteins and Heparin-Binding Components in Fetal Bovine Serum upon the Proliferation of Ectoplacental Cone Cells in Mouse Blastocysts Cultured in Vitro1

Abstract: Trophoblastic invasion of the endometrium is among the events that are crucial for successful implantation and hemochorial placentation. To understand the mechanism underlying the trophoblastic invasion, we investigated effects of fibronectin substratum and heparin-binding components in fetal bovine serum (FBS) upon trophoblast and ectoplacental cone (EPC) cells derived from mouse blastocysts produced by IVF and cultured in vitro. The results demonstrated that 1) in these blastocysts, contact of EPC cells with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…To investigate this, we isolated acinar cell clusters from control and b1 integrin-deficient pancreata and cultured them with or without FBS that contains rich ECM proteins. 19,20 b1 integrindeficient acinar cell clusters cultured with BSA showed significantly increased cell apoptosis when compared with the control cell clusters (*Po0.05; Figure 5c). However, the number of TUNEL-positive cells in b1 integrin-deficient acinar cell clusters was reduced and reached control levels when cultured with FBS medium (*Po0.05; Figure 5c).…”
Section: Significantly Reduced Amylase Expression Observed In B1 Intementioning
confidence: 95%
See 1 more Smart Citation
“…To investigate this, we isolated acinar cell clusters from control and b1 integrin-deficient pancreata and cultured them with or without FBS that contains rich ECM proteins. 19,20 b1 integrindeficient acinar cell clusters cultured with BSA showed significantly increased cell apoptosis when compared with the control cell clusters (*Po0.05; Figure 5c). However, the number of TUNEL-positive cells in b1 integrin-deficient acinar cell clusters was reduced and reached control levels when cultured with FBS medium (*Po0.05; Figure 5c).…”
Section: Significantly Reduced Amylase Expression Observed In B1 Intementioning
confidence: 95%
“…Acinar cell clusters were cultured in modified RPMI 1640 media 18 with either 1% BSA (Sigma) or 10% FBS (Invitrogen, Burlington, ON, Canada), reported to be enriched for ECM proteins, 19,20 for 24 h. Cell clusters from four experimental groups (b1KO-BSA, Ctrl-BSA, b1KO-FBS, and Ctrl-FBS) were harvested and processed for immunofluorescence with at least four mouse pancreata per experimental per group used.…”
Section: Acinar Cell Culture Experimentsmentioning
confidence: 99%
“…Attachment and Trophoblast Outgrowth Outgrowth of mouse blastocyst-derived trophoblast cells has been used as an in vitro model for implantation (Koi et al, 1995;Suenaga et al, 1996). About 70% of zona-free blastocysts attached and spread on ®bronectin-coated surface within 24 hr of culture in the absence and presence of SNP or L-NAME, except for a complete inhibition of blastocyst attachment and spread- ing at the concentration of 10 À 3 M SNP.…”
Section: Effects Of No and L-name On The Blastocystmentioning
confidence: 99%
“…The method used for assessing effects on outgrowth was the well-characterized assay established by Armant et al [30] and used by other investigators [31][32][33][34]. These studies have shown that when intact mouse blastocysts are placed in culture on fibronectin, there is a significant outgrowth of trophoblast cells.…”
Section: Blastocyst Outgrowth Assaysmentioning
confidence: 99%